OUTSOURCING DALAM PERSPEKTIF PEKERJA DAN PENGUSAHA - NFN Triyono (Research Centre for Population, Indonesian Institute of Sciences, 2011)
Regime change in Indonesia s new order into the order of the reform has given rise to policy changes, including in employment policy through the implementation of law No. 13 of 2003 on Manpower, in which set about outsourcing policy, that is still controversial among workers and employers. This occurs because of a difference of interests as well as the understanding between workers and employers. This paper aims to examine the issue of outsourcing as seen from the perspective of employers and workers on the basis of the results of the study of literature. In the implementation of the system, the working relationship has encountered various outsorcing violations. These offences are concerned, among others, the types of jobs that are outsourced, length of contract, the rights of workers who are not covered by employers as well as excluded labor outsourcing in the national social security system. Therefore it takes concrete steps· to complete outsourcing agreement involving different stakeholders, especially the aspirations of workers and employers.Keywords: industrial relations, outsourcing, labour inspection